Technological Innovations in the Production of Peruvian Television Newscasts During the Emergence of Covid-19 - Karbaum-Padilla, G. (2023)
The outbreak of Covid-19 imposed radical changes in all human activities and television journalism was no exception. This study aims to analyze the innovations that were applied by television journalists in Peru in order to continue practicing their work in one of the countries hardest hit by the pandemic. The applied methodology was qualitative, semi-structured interviews were carried out which allowed knowing the innovations that were applied to overcome the dangers and sanitary restrictions. As a result, it was obtained that the journalists hybridized their teams and production methods with non-television technologies such as video calls, mobile phones, or the implementation of telework to continue producing television news in a context for which they were never prepared.